The 2023 GEM climate survey: results and recommendations - O’Brien, Connor; Walsh, Brian M.; Vines, Sarah K.; Carr, Deborah; Segoshi, Megan (Frontiers in Astronomy and Space Sciences, 2024)
In order to help inform efforts to fulfill the National Science Foundation (NSF) Geospace Environment Modeling (GEM) community's ethical goal toward pursuing diversity, equity, inclusion, and justice (DEIJ) the authors administered the 2023 GEM Climate Survey to attendees of the 2023 GEM Workshop. Its main goals were to 1) obtain organized demographic information about the GEM community, and 2) to provide a quantitative assessment of the GEM community's perceptions of its own culture primarily with respect to inclusion and belonging. Responses indicate the GEM community is comparable or slightly more diverse than heliophysics as a whole and the American Geophysical Union (AGU) general membership, but still not close to reflecting the population of the United States or the world. The average responses to survey items about feelings of belonging in the GEM community indicate that members feel they belong in the GEM community, that the GEM community climate is broadly inclusive, and that efforts to support that cultural climate are improving over time. This is true across the entire population regardless of career stage, as well as for female respondents; Lesbian, Gay, Bisexual, Transgender, Queer/Questioning, Pansexual, Asexual (LGBTQPA+) respondents; Asian/Asian Subcontinent respondents; and non-Asian respondents of color. Division of the dataset into subgroups also indicates work to build a fully inclusive community is not complete, particularly with respect to workplace hostility these groups witness. This report recommends continuing work to capture the time history of demographics and trends in the community culture in response to inclusion efforts and initiatives.